ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI ANAK BALITA DI KELURAHAN SINDULANG SATU KOTA MANADO - Irene Natalia Papendang; Mirna Kawulusan; Nonce Nova Legi (POLTEKKES KEMENKES MANADO, 2017)
One of the International Conference On Nutrition's commitments in Rome 2014 is to eliminate hunger and prevent any form of malnutrition worldwide. Toddler nutrition status is influenced by direct and indirect causes. The direct causal factors are food intake and infectious diseases, while the underlying causes are mother's level of knowledge and history of exclusive breastfeeding. This research is to know the factors related to the nutritional status of children under five in Sindulang Urban One Kota Manado. This type of research is analytic correlation with crossectional design. Population as many as 284 balita and samples 43 under fives. Data analysis using Fisher Exact Test to know the correlation of independent and bound variable and multinominal logistic regression test to know the most dominant factor that related to nutrition status of Toddler. Instruments used in this study are questionnaires, food recall form 24 hours weighing scales, and stationery. The results of this study indicate that there are 5 children under five who have bad nutritional status (BGM) based on BB / U index, energy intake is dominated by good intake level and less, and there are 5 infants who have suffered from infectious diseases (acute diarrhea). 21 Toddlers are given Exclusive Breast Milk and 22 Toddlers are not given Exclusive Breast Milk. Most Balita women have a good level of knowledge about nutrition. There is correlation between energy intake with nutritional status of children under five (p = 0.000), there is correlation history of infectious disease with nutrient status of children under five (p = 0.007). There is no history of exclusive breastfeeding relationship with underfive nutritional status (p = 0.127). There was no correlation between maternal knowledge level and nutritional status of children under five (p = 1,000). Energy intake is the most dominant factor affecting the nutritional status of children under five in Sindulang Satu Village.